Incidencia del clima escolar en el rendimiento académico de los niños del grado 5°3 de la Institución Educativa Isabel María Cuestas González del Distrito Especial, Turístico y Cultural de Riohacha (2020)
The objective of the present investigation is to analyze the incidence that the school climate has on the academic performance of children in grade 5 3 of the Isabel María Cuestas González Educational Institution of the Special, Tourist and Cultural District of Riohacha in the classroom with in order to investigate their behavior in the academic learning and school well-being of these children. This study is framed within a type of quantitative, descriptive, correlational investigation, whose variables were analyzed based on the data obtained with Likert-type questionnaires. The data were processed using the office suite corresponding to office Excel 2013 in addition to the SPSS V20 software. The sample was carried out with 34 from grade 5 3 of the Isabel María Cuestas González Educational Institution of the Special, Tourist and Cultural District of Riohacha. It can be concluded that the school climate has several factors that directly affect academic performance, whose affirmation it occurs after the predominant data and that is the result of the data collected regarding the perception that the boys and girls have of the research. Finally, the research project requires data that establish the correlation between the variable school climate and academic performance, as well as its importance in learning development.